Analyze Factors Affecting Indonesia 10-Year Government Bond Yield Period 2021-2025 - Zulhelfi Zulhelfi (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2026)
Bond investors can calculate investment income on the funds invested in these bonds using a yield measurement tool. Yield is used, which is the primary metric investors use to assess investment profitability, aid decision-making, and assess potential risk. Bond yields and their movements reflect information about economic prospects, risks, and market functioning. This study aims to analyze the variables that influence the Indonesian 10-year government bond yield. Government bond yields are crucial economic indicators because they reflect market expectations for future growth, inflation, interest rates, and signaling economic health. Rising yields often suggest growth/inflation fears, while falling yields signal economic slowdown or demand for safety; the yield curve's shape is a powerful recession predictor. The independent variables that influence Indonesia's 10-year government bond yield analyzed in this study are inflation, the BI rate, CDS, Brent oil, the percentage change in the IDR/USD exchange rate, and the percentage change in the 10-year Treasury yield. Based on the regression analysis, this study can be concluded that the variables with positive significant effects are the BI rate, CDS, and Brent Oil, while Inflation has negative significant effects. However, the percentage change in the IDR/USD exchange rate and the percentage change in the 10-year Treasury yield did not significantly affect.